Royal Jelly—A Traditional and Natural Remedy for Postmenopausal Symptoms and Aging-Related Pathologies - Balan Andreea; Moga Marius Alexandru; Dima Lorena; Toma Sebastian; Neculau Andrea Elena; Anastasiu Costin Vlad (Molecules, 2020)
Women’s life stages are based on their reproductive cycle. This cycle begins with menstruation and ends with menopause. Aging is a natural phenomenon that a ects all humans, and it is associated with a decrease in the overall function of the organism. In women, aging is related with and starts with menopause. Also, during menopause and postmenopausal period, the risk of various age-related diseases and complaints is higher. For this reason, researchers were pushed to find e ective remedies that could promote healthy aging and extended lifespan. Apitherapy is a type of alternative medicine that uses natural products from honeybees, such as honey, propolis, royal jelly, etc. Royal jelly is a natural yellowish-white substance, secreted by both hypopharyngeal and mandibular glands of nurse bees, usually used to feed the queen bees and young worker larvae. Over the centuries, this natural product was considered a gold mine for traditional and natural medicine, due to its miraculous e ects. Royal jelly has been used for a long time in commercial medical products. It has been demonstrated to possess a wide range of functional properties, such as: antibacterial, anti-inflammatory, vasodilatative, hypotensive, anticancer, estrogen-like, antihypercholesterolemic, and antioxidant activities. This product is usually used to supplement various diseases such as cardiovascular disease, Alzheimer’s disease, sexual dysfunctions, diabetes or cancer. The main objective of this study is to highlight the e ectiveness of royal jelly supplementation in relieving menopause symptoms and aging-related diseases. We also aimed to review the most recent research advances regarding the composition of royal jelly for a better understanding of the e ects on human health promotion.
Keywords: royal jelly; bioactive properties; menopause symptoms; estrogenic e ect; apitherapy; fatty acids